Interplay of temperature and calcium content in beta-casein solutions: From controlled self-aggregation of micelles in bulk to the design of stable foams - Fameau, Anne-Laure; Houinsou Houssou, Bérénice; Riaublanc, Alain; Cousin, Fabrice (Frontiers in Soft Matter, 2022)
We describe in this study the aggregation behaviour of β-casein micelles from milk in bulk aqueous solution as function of both temperature and calcium content, and its influence on the foaming properties, in order to test if the different aggregation states of β -casein makes possible the design of proteins-based thermoresponsive foams. First, we characterized the morphology of the self-assembled β-casein molecules in solution by coupling turbidity measurements, Dynamic Light Scattering (DLS) and Small Angle Neutron Scattering (SANS). They self-organize into isolated micelles at low temperature (20°C) whatever the calcium content, and transit in a reversible way into aggregates of micelles at large temperature in presence of calcium, with a threshold transition that depend both on temperature and calcium content. The micelles aggregation is driven by the calcium through association with serine phosphate groups localized on the hydrophilic part of the -casein. In the micelles regime, we demonstrated that the addition of calcium tunes the aggregation number of unimers per micelle in the same way than an increase of temperature through a change of hydrophobic interactions. The hydrophilic chains of the corona are however in a good solvent and interact through excluded volume interactions, even when the β-casein micelles aggregates themselves. The internal molecular structure of the micelles is thus not modified by calcium bridges, which explains the complete reversibility of the aggregation process over temperature cycling. Second, we studied the foam stability versus time as a function of the temperature and calcium content by measuring the kinetic evolution of both the foam volume and the liquid fraction. Foams produced by solutions containing only β-casein micelles were stable in terms of foam volume on a timescale of 1 hour at 20°C but drained quickly. However, foams become unstable when the temperature was increased above 20°C. In presence of calcium, the aggregation of -casein micelles inside the foam liquid channels enabled to increase foam stability at larger temperature by acting as a cork, which slows down the drainage. The increase of foam stability by such aggregates is however not sufficient on the long term to allow the design of thermoresponsive foams.